URBAN GEOTOURISM: GOVERNANCE IN THE NEW NORMAL - WULUNG, SHANDRA RAMA PANJI; ABDULLAH, CEP UBAD; MAHARANI, GANESIA DIFTA; FADILAH, MUHAMAD AQSAL NUR; CHOESSAWATI, MAUDHY DHANTY; RAHAYU, AISYAH NYTYA EUDORA (Program Studi Pariwisata, UPN Veteran Jawa Timur, 2022)
The North Bandung area is a protected area and a tourism destination, this triggers high tourist visits. The existence of the Covid-19 pandemic has triggered destination managers to innovate, especially in tourists’ management. The purpose of the research is to identify tourism governance since the new normal era. In addition, this study also takes an inventory of tourist attractions and interprets them as urban geotourism. This research was conducted from February to July 2021 in the Taman Hutan Raya area of Ir. H. Djuanda. The qualitative approach in this research with primary data acquisition through observation and interviews, while secondary data obtained through policy documents related to tourism. An online interview was conducted through the zoom meeting application to the manager of Taman Hutan Raya Ir. H. Djuanda in finding information related to the implementation of tourism governance during the new normal. Online interviews with geotourism experts from a local university, were also conducted. The informants were selected using the purposive sampling technique. Content and descriptive analysis are the analytical techniques in this study on the data obtained. The results showed that the tourist attraction in Taman Hutan Raya Ir. H. Djuanda has the potential as a geotourism attraction. Curug Dago is one of urban geotourism attraction in Bandung City. Manager of Taman Hutan Raya Ir. H. Djuanda innovated during the pandemic by distributing entrance tickets through digital media. In addition, the manager also makes other innovations by collaborating with third parties in creating new tourist attractions in the new normal era. Keywords: Geotourism, New Normal, Taman Hutan Raya Ir. H. Djuanda, Tourism Governance